2013
DOI: 10.1016/j.gtc.2013.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopy Quality

Abstract: Synopsis Colonoscopy is an excellent area for quality improvement 1 because it is high volume, has significant associated risk and expense, and there is evidence that variability in its performance affects outcomes. The best endpoint for validation of quality metrics in colonoscopy is colorectal cancer incidence and mortality, but because of feasibility issues, a more readily accessible metric is the adenoma detection rate (ADR). Fourteen quality metrics were proposed by the joint American Society of Gastroint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 82 publications
(90 reference statements)
0
11
0
1
Order By: Relevance
“…Although some endoscopists challenge the association between withdrawal times and PDR/ADR (as increasing withdrawal time alone will not improve an ADR/PDR that is already adequate), data suggest that longer withdrawal times are strongly associated with an increase in PDR and ADR, particularly when endoscopists do not achieve accepted benchmarks. [1,13,19,21] Another factor that could have affected our PDR/ADR was the adequacy of our outpatient bowel preparation, which was below the ASGE/ACG Task Force benchmark of ≥85%. Interestingly, our results showed that inadequate bowel preparation yielded similar PDRs and ADRs to adequate bowel preparation, which could indicate that we are 'over-calling' poor bowel preparation as opposed to it actually being inadequate.…”
Section: Discussionmentioning
confidence: 99%
“…Although some endoscopists challenge the association between withdrawal times and PDR/ADR (as increasing withdrawal time alone will not improve an ADR/PDR that is already adequate), data suggest that longer withdrawal times are strongly associated with an increase in PDR and ADR, particularly when endoscopists do not achieve accepted benchmarks. [1,13,19,21] Another factor that could have affected our PDR/ADR was the adequacy of our outpatient bowel preparation, which was below the ASGE/ACG Task Force benchmark of ≥85%. Interestingly, our results showed that inadequate bowel preparation yielded similar PDRs and ADRs to adequate bowel preparation, which could indicate that we are 'over-calling' poor bowel preparation as opposed to it actually being inadequate.…”
Section: Discussionmentioning
confidence: 99%
“…Adenoma detection rate (ADR) is the most validated measure of colonoscopy quality. [4] Lower physician ADR is associated with higher rates of interval colorectal cancer. [5] In a recent modeling study by Meester at al, a 5% decrease in ADR was associated with a 12.3% and 13.3% increase in colorectal cancer incidence and mortality, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Quality reporting in colonoscopy is increasingly required to maintain public confidence. Health system management depends on metrics that are continually evaluated and associated with clinical outcomes and benchmarks [ 51 ]. Failure to allocate scarce resources based on access requirements and care quality can lead to misaligned incentives and poor outcomes.…”
Section: Discussionmentioning
confidence: 99%